Economic growth, convergence, and world food demand and supply - Fukase, Emiko; Martin, Will (World development, 2020)
•Income convergence embodied in the widely used economic projections increases world food demand to 2050 by about a third.•Higher rates of convergence increase food demand by more than supply, resulting in upward pressure on world food prices.•Resource-cost measures capture the agricultural effort needed to meet food demand better than those of calories consumed.•Per capita food demand growth is likely to be a more important driver of food demand to 2050 than population growth. In recent years, developing countries have been growing much more rapidly than the industrial countries. This growth convergence has potentially very important implications for world food demand and for world agriculture because of the increase in demand for agricultural resources as diets shift away from starchy staples and towards animal-based products and fruits and vegetables. Using a resource-based measure of food production and consumption that accounts for the much higher production costs associated with animal-based foods, this article finds per capita demand growth to be a more important driver of food demand than population growth between now and 2050. Using the middle-ground Shared Socioeconomic Pathway scenario to 2050 from the International Institute for Applied Systems Analysis, which assumes continued income convergence, the article finds that the increase in food demand (102 percent) would be about a third greater than under a hypothetical scenario of all countries growing at the same rate (78 percent). As convergence increases the growth of food supply by less than demand, it appears to be a driver of upward pressure on world food prices.